A Lexical Morphological Analysis of Nicknames in Ng'umbo - A Dialect of Bemba, Zambia - Kabaso, Fredgerious; Mambwe, Kelvin (Daengku: Journal of Humanities and Social Sciences Innovation, 2025)
N’gumbo, a dialect of Bemba, is predominantly spoken in the Luapula and Copperbelt provinces of Zambia. This dialect is characterized by various types of nicknames that reflect its speakers' shared experiences, values, and beliefs. This study aims to analyze the morphological structures of selected nicknames within the N’gumbo dialect. Using a sample of 60 nicknames gathered through document analysis, interviews, and self-introspection, the study demonstrates that these nicknames exhibit distinct morphological structures primarily influenced by the morphology of Bantu languages. The analysis identifies several structures, including: stem only, prefix, stem with a final vowel, root with a final vowel, and combinations of prefixes and stems. Additionally, the study recognizes structures related to denominals, deverbals, and de-adjectival forms. Furthermore, some nicknames were found to be neologisms (newly created terms) or derived from loanwords. The study involved eight (8) participants to gather nicknames and their meanings, alongside insights from one of the researchers, who is a speaker of the dialect. The analysis was anchored in lexical morphology, allowing for the segmentation of nicknames as lexemes of the dialect, thus facilitating a clearer analysis and interpretation of the data.